192 CONNECTED HEALTH SUSTAINING HOME STAY IN DEMENTIA (CHESS): 12-MONTH TRAJECTORY OF QUALITY OF LIFE IN PEOPLE WITH DEMENTIA. (25th October 2022) - Merriman, N; Mackey, L; Fernandez, EG; Curran, F; Caulfield, B; Power, D; O'Shea, D; Doyle, R; Blake, C
Abstract: Background: Research is needed to examine how Quality of Life (QoL) changes as dementia progresses. We explored QoL trajectories over a 12-month period and examined factors that influence QoL in People with Dementia (PwD). Methods: Fifty-two PwD and their informal caregivers participated in the "CHESS" Study. Data were collected at five time points over 12 months between April 2017 and November 2019. Mixed-model analyses were used to investigate associations of self-rated QoL and caregiver-rated QoL (measured by the DEMQoL and DEMQoL Proxy, respectively) with factors in four domains: 1) Psychological Well-Being (PWB; measures of anxiety and depression); 2) Social Capital and Resources (SCR; incorporating access to community-based health services, education level, occupation and living situation of the PwD, employment status of the caregiver); 3) Physical Fitness and Health (PFH; including the Quantitative Timed Up and Go (QTUG), baseline grip strength, indices of frailty, sensory acuity); and Managing Everyday life with Dementia (MED; incorporating measures of cognition, behavioural disturbances, functional ability, indices of dependence of PwD). Results: Across all domains, caregivers' ratings of QoL for PwD decreased over time (p=0.012). In PWB, greater levels of depression (p=0.007) and anxiety in the PwD (p<0.001) predicted lower self-rated QoL, and higher caregiver anxiety levels predicted lower caregiver-rated QoL (p=0.012). In PFH, having a caregiver administer medication (p=0.03) was associated with higher self-rated QoL. Interestingly, caregiver-rated QoL was higher for PwD who took longer to return to sitting during the QTUG (p=0.043). In MED, being independently mobile (p=0.012) predicted higher self-rated QoL. No other factors within the SCR domain reached significance in predicting QoL. Conclusion: This longitudinal analysis elucidates potential predictors of QoL in PwD. Psychological well-being in PwD and their caregivers was shown to significantly impact on QoL, and so, these factors should be routinely included in future research studies and clinical assessments.